Restoration of Gottseelige Schluess und Fuersaetz der Seele, an eighteenth century vellum bound book - Margit J. Smith (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The article concerns the complete restoration of an 18th century vellum bound book printed in Würzburg. All work was done during a workshop at the Centro del bel libro in Ascona, Switzerland, under the direction of Ms Renate Mesmer. To preserve as much as possible of the original book, the least invasive techniques were applied in repairing paper, vellum, and the endbands, but the bookblock had to be disbound and re-sewn completely. In a new method, the vacuum table was used to force the Yapp edges back to their original 90-degree. To repair a circular hole in the cover, the replacement vellum was skived on the hair-side in contrast to usually skiving on the flesh-side, using a glass shard in addition to the skiving knife.